Long Term Consequences of Infliximab among a Sample of Spondyloarthropathic Patients Attending Baghdad Teaching Hospital - Atta Ah mousa Al-Sarray (Journal of Global Pharma Technology, 2018)
Objective: To determine LFT, lipid profile and the increase in weight after one year of infliximab treatment among a sample of spondyloarthopathic patients attending ‘Baghdad teaching hospital’   Patients &Methods: prospective study was carried out for a period of one years  In Baghdad teaching hospital(biological unit) on 1st of January  2016 and ending on December 2017 .A total of 120 cases Anky losing  and psoriatic arthritis on biological agent(infliximab) had two reading of liver function test  , lipid profile  and body mass index first reading at( zero week)  and second reading at (one-year) after biological agents . Results: The mean age of study sample 36±10.3,mean age of onset 29±11.5and duration 11±8.5Significance abnormality of liver function test (ALT,AST and AP) at two reading (baseline and after one year of biological agent( p=0.0001).Regarding total Cholesterol , Triglycerides ,High Density Lipoprotein & Low density  Lipoprotein (TC,TG, HDL-c and LDL-c) Significance differences(p<0.0001) were seen  after biological  therapy in study sample. Significance differences were seen regarding body mass index and weight gain after one year of follow up of patients. Conclusion: Significance rise of LFT, abnormal lipid profile and weight increment in the study sample after one year of follow up after infliximab therapy in patients with spondyloarthopathy. Recommendation: Our findings suggest the need for more prospective studies regarding the relative contribution of infliximab treatment for abnormal Liver function test, Lipid profile and weight gain Keywords: Patients, Infliximab, Anti-TNF agents.